CISÃO MECÂNICA DE POLÍMEROS FLEXÍVEIS NA REDUÇÃO DE ARRASTO EM ESCOAMENTOS TURBULENTOS ATRAVÉS DE CONTRAÇÕES - Silva, Ivanor Martins da (2021)
This work presents an experimental study of drag reduction (DR) in turbulent flow by addition of polymers, specifically addressing polymeric degradation in fitting pipes (abrupt contractions). There are many studies in the literature on drag reduction in pipe, however, these studies generally assess the polymeric degradation as a whole in the pipe, that is, including pump, straight pipe, bends, tees, valves and reductions, without specifically evaluating the accessory. The practical application of drag reduction in long pipelines or industrial pipes makes it interesting to investigate how important the degradation in the accessories is in relation to the straight sections. Drag reduction in pipe fittings is still a relatively poorly studied topic. The objective of this work is to evaluate the conditions in which the polymer chain breaks in turbulent flow and the parameters that influence this important phenomenon. The evaluation of polymeric degradation in abrupt contractions is done on an experimental apparatus composed of tubes in series, with an internal diameter equal to 16.5 mm. Contractions with diameter ratio of 2x1 and 1.5x1 are used. In these tests, solutions of polyethylene oxide (PEO) diluted in filtered water are used, with concentrations of 25, 50, 100 and 200 ppm on mass basis. In order to evaluate the effect of molecular weight, Mv, on drag reduction, polymers with Mv, = 1.0 x 106 , 2.0 x 106 , 5.0 x 106 e 8.0 x 106 g/mol are used. The flow is driven by a compressor and the tests are carried out at constant pressure, with Reynolds number between 70,000 and 90,000. This study also evaluates the relationship between polymeric degradation, intrinsic viscosity and molecular weight, Mv. The study shows a reduction in Mv when DR falls due to mechanical degradation of the polymer. The loss of DR efficiency is quantified here, when there is an abrupt contraction in the pipeline, and it is found that this loss is significantly greater than when there is only a straight tube. A mathematical model is proposed to describe the drag reduction coefficient, DR, as a function of four variables: number of passes, Np, concentration of polymeric solution, c, molecular weight, Mv, and geometric factor, G. The relationship between the drop in DR and the drop in molecular weight is described. Finally, the molecular weight values of the degraded solution are obtained by measuring the intrinsic viscosity, using the Mark-Houwing equation.